KESATUAN SURAT AL-QUR’AN DALAM PANDANGAN SALWA M.S. EL-AWWA - Adrika Fithrotul Aini (Program Studi Ilmu Al-Qur’an dan Tafsir Fak. Ilmu Agama Islam Universitas Islam Indragiri, 2015)
Munasabah is one of the Quranic sciences which undergoes development. Thus, this article will discuss this munasabah, or integral surah in the Qur-an based on Salwa el-Awwa’s approach. It explains the theory by using the descriptive method. It resultsthat the new concept offered by Salwa concerning Quranic Munasabah explains her curiosity toward developing integrated surah in the Quran. This concept is aimed at dividing the themes of thesurah objectively and not intuively. So, the theory in orderingunity of Quranic surah is based on coherence and relevanceby using pragmatic approach.Keywords: Munasabah, Coh